‘Requiem for the Bloody Date Trees’: Government-Media Relations in Iran and the Earthquake in the City of Bam - Sadan, Amit (Jama'a: an Interdisciplinary Journal of Middle East Studies, 2019)
In this article I examine discursive developments regarding the earthquake that struck southeast Iran on December 26, 2003. This natural disaster destroyed much of the city of Bam, and left tens of thousands of casualties. In comparison with numerous studies from various fields, such as engineering and civil society, few studies have addressed the conduct of media outlets during the Bam crisis. My study has two goals: first, I will delineate the practical developments following the disaster. Second, I will analyze the events’ local press coverage. This study will shed light on the power dynamics between the state and the media in the years 1997-2005, considered to be the period of reform in Iran. My findings show that the ruling establishment restricted the state-owned press, thus portraying the disaster in a manner agreeable to the regime’s legitimacy. This examination equally underlines limits of the state’s power, demonstrating alternative modes of expression in social spaces beyond the regime’s reach.